TOP MANAGEMENT SUPPORT TO CLIMATE CHANGE - Neto, Siqueira de Morais; Pereira, Maurício Fernandes (Contextus - Revista Contemporânea de Economia e Gestão, 2014)
The article theme is the Corporate Climate Change and aims to identify whether there is top management support to the companies’ attitudes related to the climate change, with a comparison between two groups of enterprises, “Brazil” and “S&P 500 MZ”, using the Carbon Disclosure Project database. It was used a methodology of a descriptive nature based on secondary data collection, which was done through literature review and the observation of the CDP’s questionnaires. It was observed that 62% of the Brazilian companies and 66% of the American corporations analyzed stated that they have an executive body with overall responsibility for dealing with climate change.